2011
DOI: 10.1158/0008-5472.can-11-0362
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Glucocorticoid Receptor Is Associated with Poor Prognosis in Estrogen Receptor-Negative Breast Cancer

Abstract: Estrogen-negative (ER−) breast cancers have limited treatment options and are associated with earlier relapses. Because glucocorticoid receptor (GR) signaling initiates anti-apoptotic pathways in ER− breast cancer cells, we hypothesized that activation of these pathways might be associated with poor prognosis in ER− disease. Here we report findings from a genome-wide study of GR transcriptional targets in a pre-malignant ER− cell line model of early breast cancer (MCF10A-Myc) and in primary early-stage ER− hum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
259
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(282 citation statements)
references
References 55 publications
21
259
2
Order By: Relevance
“…In addition, the GR has recently emerged as a candidate tumor suppressor gene in breast cancer (44). Earlier studies had found GR somatic aberrations with an attendant altered transcriptional profile in triple-negative breast cancer (45), and more recently, a complex association between GR expression in breast cancer, predicting either a poor or good prognosis dependent on subtype (46). Taken together our findings reveal an important role for GR in regulating mitotic progression, aneuploidy, and tumorigenesis.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, the GR has recently emerged as a candidate tumor suppressor gene in breast cancer (44). Earlier studies had found GR somatic aberrations with an attendant altered transcriptional profile in triple-negative breast cancer (45), and more recently, a complex association between GR expression in breast cancer, predicting either a poor or good prognosis dependent on subtype (46). Taken together our findings reveal an important role for GR in regulating mitotic progression, aneuploidy, and tumorigenesis.…”
Section: Discussionsupporting
confidence: 66%
“…It is a well-known fact that the combinatorial expression of all the NRs is important in determining the prognosis and avenues for the treatment [21,22]. However, fewer studies have been carried out on the expression of all the steroid hormone receptors by examining the action of one hormone at a time, and mostly a reductionist approach was used [23].…”
Section: Discussionmentioning
confidence: 99%
“…In ER+ breast cancers, high GR expression is associated with better survival (Pan et al 2011, Abduljabbar et al 2015b, whereas in ER− breast cancers, high GR expression is correlated with poorer breast cancer-specific survival (Pan et al 2011, Abduljabbar et al 2015b.…”
Section: Nr Expression In Breast Cancer Subtypesmentioning
confidence: 99%